Ordenen Stjernen i Øst og julens budskap - Gilhus, Ingvild Sælid; Mikaelsson, Lisbeth (Tidsskrift for kulturforskning, 2017)
The article is based on a close reading of the Christmas issues of the Norwegian theosophical magazine Stjernebladet/Stjernen in order to examine its approach to Christmas. The magazine was the mouthpiece of the Norwegian branch of the Order of the Star in the East (1910-1929). This fellowship was established within Theosophical Society in order to prepare its members for the imminent appearance of the theosophical messiah, the Indian youth Krishnamurti. He was thought to be a reincarnation of the so-called world teacher, who according to theosophical doctrine had incarnated before in such figures as Buddha and Christ. Our study showed that in Stjernebladet/Stjernen the Christian myth of the birth of Christ was used as an allegory for central ideas in theosophical messianism.